Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fmed.2020.00006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Natural and Botanical Medicines for Activity Against Growing and Non-growing Forms of B. burgdorferi

Abstract: Lyme disease is the most common vector-borne disease in the US and Europe. Although the current recommended Lyme antibiotic treatment is effective for the majority of Lyme disease patients, about 10-20% of patients continue to suffer from persisting symptoms. There have been various anecdotal reports on the use of herbal extracts for treating patients with persisting symptoms with varying degree of improvements. However, it is unclear whether the effect of the herb products is due to their direct antimicrobial… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 117 publications
0
37
0
Order By: Relevance
“…The Cmax concentration we used was taken from a pharmacokinetic study in mice. We realize that the Cmax concentration we used in this study for Cry was extremely low (0.024 µg/mL) when compared to all other antibiotics tested and that the study from which we took the Cmax value was conducted with only two mice [33]. We think further pharmacokinetic studies of Cry should be performed in order to evaluate a more exact Cmax value, evaluate the potential toxicity of this compound, and determine its potential use for LD.…”
Section: Discussionmentioning
confidence: 99%
“…The Cmax concentration we used was taken from a pharmacokinetic study in mice. We realize that the Cmax concentration we used in this study for Cry was extremely low (0.024 µg/mL) when compared to all other antibiotics tested and that the study from which we took the Cmax value was conducted with only two mice [33]. We think further pharmacokinetic studies of Cry should be performed in order to evaluate a more exact Cmax value, evaluate the potential toxicity of this compound, and determine its potential use for LD.…”
Section: Discussionmentioning
confidence: 99%
“…Research over the past few decades has demonstrated that many botanical medicines have antimicrobial, antiparasitic, and anticancer activity ( Tagboto and Townson, 2001 ; Shoemaker et al., 2005 ; Feng et al., 2011 ). In our previous study, we identified seven herbal medicines that have good activity against stationary phase Borrelia burgdorferi compared to the control antibiotics used in clinical treatment ( Feng J. et al., 2020 ). In humans, Babesia spp.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicated that natural products extracted from plants and herbs may serve as a potential source of promising compounds for anti-parasitic drugs. In this current study, we used the same hamster erythrocyte model to screen for inhibition of B. duncani using a panel of 46 herbal medicine extracts, many of which are useful in the treatment of babesiosis and related conditions according to the Buhner book on herbal medicines ( Buhner, 2015 ) or were shown in our previous in vitro studies to have antimicrobial effects ( Feng J. et al., 2020 ). Our results identified Cryptolepis sanguinolenta, Artemisia annua, Scutellaria baicalensis, Alchornea cordifolia , and Polygonum cuspidatum and their bioactive compounds as having good activity against B. duncani .…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that future studies should be directed at identifying the active constituents of each botanical, evaluating synergistic combinations, and confirming their safety and efficacy. 13 Continuing with antibiotic treatment may affect the immune system in a variety of other ways. Bernardino et al did a study on monkey brain cells stimulated with LD bacteria and showed that doxycycline moderated the inflammatory response.…”
mentioning
confidence: 99%
“…The authors concluded that future studies should be directed at identifying the active constituents of each botanical, evaluating synergistic combinations, and confirming their safety and efficacy. 13 …”
mentioning
confidence: 99%